Computational intelligent data analysis for sustainable development - Yu, Ting, 1975-; Chawla, Nitesh V.; Simoff, Simeon (Boca Raton : Taylor & Francis, 2013)
"Intelligent data analysis techniques offer powerful solutions to collecting and analyzing vast quantities of environmental and economic data, which lead to better decision making for sustainable development. This volume is the first to discuss the treatment of intelligent data analysis techniques in sustainable development applications. The book describes the emerging use of data mining, machine learning, artificial neural networks, data visualization, knowledge discovery, GIS, and other technologies to tackle environmental, economic, and social issues, including climate change, risk management, and population growth"--
section 1. Integrated sustainability analysis -- section 2. Computational intelligent data analysis for climate change -- section 3. Computational intelligent data analysis for biodiversity and species conservation -- section 4. Computational intelligent data analysis for smart grid and renewable energy -- section 5. Computational intelligent data analysis for sociopolitical sustainability.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Sustainable development -- Data processing; Public works -- Planning -- Data processing; Social policy -- Data processing; Environmental quality -- Mathematical models; Data mining; Electronic books